Pengaruh Ukuran Perusahaan Dan Likuiditas Terhadap Kebijakan Dividen Di Perusahaan LQ45 - Willyam Eka Pratama; Dewi Zulvia (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine and analyze the effect of frimsize and liquidity on dividend pay ratio in LQ45 non-finance companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population of this study are 45 companies included in the LQ45 index category. With the proposive sampling method, the samples obtained were 13 companies. The data testing method used is panel data regression. Based on the test results, it is known that company size and liquidity have a significant effect on dividend policy in LQ45 non-finance companies for the 2017-2021 period.